Control Patterns Among Multinational Subsidiaries in Malaysia - Raja Yusof, Raja Nerina (2003)
Malaysia is currently one of the competitive recipients of foreign direct investments in the Asian region. The stable political and economic environment of the country have attracted foreign multinational corporations (MNCs) to choose and set up business here in Malaysia, hence contributing to her economic growth and development. This research presents the findings of a survey on foreign subsidiaries in Malaysia, regarding their foreign parents' control patterns over them. Control patterns in this study are divided into two types of control. Behavioral control is mainly the direct control imposed by the foreign headquarters and is measured by the number of expatriates representing the foreign parent in key positions of the local subsidiary. On the other hand, output control reflects indirect or "hands-off" approach of headquarters and is gauged by the frequency of reports submitted to foreign headquarters annually. This research analyses how these control patterns are associated with the nationality of the foreign parent organization, as well as the level of ownership of foreign parent in a Malaysian subsidiary. Control patterns are also linked to a third variable, which is the typology of MNCs that is employed by a foreign parent organization. After receiving feedback from 113 MNCs in Malaysia, the findings support that Japanese MNCs do practice more behavioral control than their European or American counterparts. However, the hypothesis that American MNCs practice more output control than their Japanese or European counterparts is not supported. As for the level of ownership, one out of two hypotheses is accepted. The analysis indicates that the level of ownership of foreign parent in the Malaysian subsidiary and the use of behavioral control are dependent. On the other hand, the analysis did not discover enough evidence to support that there is a difference in the usage of output control among wholly, majority or minority owned subsidiaries.Typology of MNCs in this study is divided into two broad categories: global and non-global. Findings indicate that behavioral control and typology of MNCs are dependent. However, the study failed to find significant evidence that points to a difference of output control usage between the two types of MNCs.